„We Give Birth to Life Assisted by Death” — on Mothers and Daughters in Anna Świrszczyńska’s and Anna Kamieńska’s Poetry - Pawlik, Aleksandra (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The article is devoted to comparative interpretation of Anna Świrszczyńska’s and Anna Kamieńska’swork. Using the studies on death category in poems related to birth, motherhood and the bodily relationsof poems’ heroines with their parents, the author of this report demonstrates that by giving birth toa child, woman marks the newborn with the element of death.Both Świrszczyńska and Kamieńska draw from traditional symbols of death and contemporarysomatic metaphorics in their poetry, including abject aesthetics. From this perspective, a group of textsdedicated to the poet’s deceased parents has extreme relevance. Birth and death motifs in the poems are closely related to woman’s fate and maternal ambivalence.Such presentation ultimately leads to questions about the meaning of human existence.Acknowledging the differences between Świrszczyńska’s and Kamieńska’s work, the paper proves thatboth authors depict the confrontation of the joy of parenthood with physiology, a constant reminder ofthe frailty of life and the pain inherent in each individual’s existence.The paper’s methodology is based on the theory of „existential opening” (Jolanta Brach-Czaina, TheCracks in Existence), loathing (Julia Kristeva, Powers of Horror) and boundary situations (Karl Jaspers,Boundary Situations).